Pengaruh Literasi Keuangan dan Gaya Hidup Terhadap Perilaku Konsumtif Mahasiswa: Studi Kasus pada Mahasiswa Fakultas Ekonomi Universitas Negeri Gorontalo - Rahma Mohi; Raflin Hinelo; Dewi Indrayani Hamin (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to examine the influence of financial literacy and lifestyle on student’s consumptive behavior in the Faculty Of Economics, Universitas Negeri Gorontalo. A quantitative study method with a correlational design was employed. The study population consisted of students of the Faculty of Economics, Universitas Negeri Gorontalo, from the 20192023 cohorts, with a sample size of 100 respondents selected using quota sampling. Data were collected through questionnaires that had undergone validity and reliability testing. The data were analyzed using multiple linear regression, normality tests, heteroscedasticity tests, multicollinearity tests, and hypothesis testing, facilitated by IBM SPSS version 22. The study findings indicate that: (1) no significant influence of financial literacy on the consumer behavior of students of the faculty of economics, universitas negeri Gorontalo is found. It obtains a significanse value of 0.421  0.05 and t count is smaller than t table or -0.808 < 1.986. (2) A significant influence of lifestyle on the consumer behavior of students of the faculty of economics, universitas negeri gorontalo is found. This result obtains a significance value of 0.000 < 0.05 and t count is greater than t table or 7.959 > 1.986. (3) A significant influence between financial literacy and lifestyle on consumer behavior of students of the faculty of economics, universitas negeri gorontalo is found with a significanse value of 0.000 < 0.05 and F count value of 31.986, which means F count > F table or 31.986 > 3.09.